(untitled) (Bangladesh Journal of Botany, 2025)
In the assessment of treatments for management of mustard aphid, it was observed that Neemazal T/S 10,000 ppm (T4) application was the most effective among phyto extracts resulting in the lowest aphid population (15.26 and 7.48 mustard aphid/10cm central twig in first and second spray population, respectively) and yielding the highest output of 12.71 q/ha following closely to T3, which yielded 11.94 q/ha. The treatment T4 also generated the highest net return (Rs. 23927.33/ha) and cost-benefit ratio (1:9.97), trailed by T3 (Rs.20233.58/ha and 1:9.28). Other treatments ranked in terms of effectiveness include, Dashparni ark @ 3% (T1), Lantana camera leaf extract @ 5% (T6), Mixed leaf extract @ 3% (T2), Garlic extract @ 5% (T8), and Parthenium leaf extract @ 5% (T5). Treatment T7 was found the least effective among those tested. As for the standard check, Imidacloprid 17.8 SL @ 0.05% (T9) exhibited the most significant impact with a yield of 13.87 q/ha, net return of ₹29851.67/ha and a cost-benefit ratio of 1:12.98. Bangladesh J. Bot. 54(2): 261-267, 2025 (June)